Microbial hazards and control in the preparation and vending of rellenong bangus - Valdezco, Rachelle Garcia
ABSTRACT This study applied the HACCP concept in the preparation, storage and retail-vending of the most popular fish dish in a representative small-scale fastfood establishment. It was conducted as part of the University of the Philippines Office of Research Coordination (UP ORC) Research Project No. 09808 Ns entitled: "Applications of Hazard Analysis and Critical Control (HACCP) System to Small-scale Fastfood Establishments" under Dr. Ma. Patricia V. Azanza. Rellenong bangus was identified in a consumer survey in the College of Arts and Sciences Alumni Association (CASAA) foodcourt as the test product. It was used for all the succeeding examinations conducted for quality assessment. A foodflow diagram was developed and the general operations in the foodflow were: pre-cooking of the raw materials, cooking of the dish, transporting of the cooked dish from the kitchen to a foodstall in CASAA, retail-vending and hold-on display. Sampling points were then determined which included the uncooked fish, cooked stuffing, stuffed fish, and fish samples during hold-on display for 6 h. Results of quality assessment were the used to identify the microbial hazards and critical control points in the foodflow. The microbial profile of rellenong bangus was established from the starting raw materials until the finished product was vended in one of the foodstalls in the test foodcourt were as follows: TPC of 〖10〗^2-〖10〗^4 cfu/g. Sources of microbial hazards identified in the foodflow of rellenong bangus included natural contamination of the raw materials, contamination from food contact surfaces and the hands of the food handlers. Critical points identified in the foodflow were the control of time and temperature during cooling of the boiled meat and cooked stuffing prior to flaking and manual stuffing, respectively. Hygienic stuffing, cooking temperature during the vending operations were also considered critical control points. It was recommended that source of the test food should obtain raw materials of high microbial quality standards. Also, observance of proper time and temperature during the operational steps and observance of good hygienic practices from the time of preparation until the vending of the test food were suggested.